Health care and harm reduction provider perspectives on treating older adults who use non-medical opioids: a qualitative study set in Chicago - Maryann Mason; Lori Ann Post; Rahul Aggarwal (BMC, 2023)
Abstract Background Opioid overdose death rates are increasing for adults aged 55 and older, with especially high rates in large urban areas. In parallel, admissions to treatment programs for older adults using illicit substances are increasing as well. Despite these trends, there is a lack of information about older adults who use non-medical opioids (NMO) and even less knowledge about their health and service encounters. Conducted in Chicago, Illinois, this qualitative study explores the perspectives of health care and harm reduction service providers who work with older adults using non-medical opioids. Methods The study used snowball sampling to locate participants with expertise in working with older adults who use non-medical opioids. In total, we conducted 26 semi-structured interviews from September 2021-August 2022. We explored questions regarding participants' perceptions of older adult opioid use patterns, comorbidities, and involvement in harm reduction outreach and opioid use disorder treatment. Results Many of the providers we interviewed consider older adults who use NMO as a distinct population that employ unique use behaviors with the intent to protect them from opioid overdose. However, these same unique behaviors may potentiate their risk for overdose in today's climate. Providers report initial encounters that are not care seeking for opioid use and primarily oriented around health conditions. Older adults who use non-medical opioids are seen as complex patients due to the need to diagnostically untangle symptoms of substance use from co-morbidities and conditions associated with aging. Treatment for this population is also viewed as complicated due to the interactions between aging, comorbidities, and substance use. Providers also noted that older adults who use NMO have use behaviors that make them less visible to outreach and treatment service providers, potentially putting them at increased risk for overdose and health conditions associated with opioid use. Conclusions Findings from this study are intended to inform future research on care provision for older adults who use non-medical opioids and may be especially applicable to large urban reas with histories of opioid use dating back to earlier drug epidemics of the 1970s, 1980s, and 1990s.